Pengaruh Implementasi Manajemen Kurikulum dan Kinerja Guru terhadap Peningkatan Penjaminan Mutu Pendidikan Segregasi di SLB BC Cempaka Putih - Isti Haryani (Jurnal Gentala Pendidikan Dasar, 2022)
This study aims to examine and analyze the effect of curriculum management implementation and teacher performance on the Improvement of Segregation Education Quality Assurance in SLB BC Cempaka Putih. The research method used in this research is descriptive analysis method with survey, interview, and observation techniques. While the data analysis technique used to answer the hypothesis of this research is statistics with a path analysis model. The population as well as respondents in this study were all 52 teachers of SLB BC Cempaka Putih. Technical analysis of the data used to test the hypothesis is simple regression analysis with multiple regression, t test and F test. The results show that 1) there is an effect of curriculum management implementation on improving the quality assurance of segregation education in SLB BC Cempaka Putih by 44.32%, which means that the two variables go hand in hand, the more effective the implementation of curriculum management, the better the improvement in quality assurance. 2) there is an effect of teacher performance on increasing the quality assurance of segregation education in SLB BC Cempaka Putih by 43.80%, meaning that the more maximal the teacher's performance is, the higher the effect on improving education quality assurance. 3) there is an effect of curriculum management implementation and teacher performance on improving the quality assurance of segregated education in SLB BC Cempaka Putih by 45.23%, both curriculum management variables and teacher performance go hand in hand with education quality assurance, which means more effective curriculum management implementation and teacher performance the higher the increase in education quality assurance. The results of testing the main hypotheses in this study can be concluded that the implementation of curriculum management and teacher performance has a positive and significant impact on the Improvement of Segregation Education Quality Assurance in SLB BC Cempaka Putih.